Measurement uncertainty associated with shipboard sample collection and filtration for the determination of the concentration of iron in seawater. Issue 37 (25th August 2016) - Clough, Robert; Floor, Geerke H.; Quétel, Christophe R.; Milne, Angela; Lohan, Maeve C.; Worsfold, Paul J.
Abstract : ANOVA used to determine uncertainty associated with the way in which deep, open ocean seawater samples were collected and conditioned (filtered). Abstract : A flow injection with chemiluminescence detection (FI-CL) method was used to determine the concentration of dissolved iron in seawater samples collected in the South Atlantic during the GEOTRACES GA10 cruise that took place from 24th December 2011–27th January 2012 on board the R.R.S. James Cook (cruise JC068). Six different sample collection and filtration strategies were used. Open ocean (shallow and deep) and coastal (shallow and deep) samples were collected and five sub-samples from each collection were filtered through a cartridge filter. For the deep open ocean sample, separate sub-samples were also filtered through a membrane disc filter. In addition, deep open ocean sub-samples were also taken from five separate sampling bottles. Each sub-sample (29 in total) was analysed six times (giving 174 discrete measurements in total) and the within sub-sample precision was in the range 1.4–12.2%. There was no statistically significant difference for the deep, open ocean sample between the mean results obtained with the two different filter types or the single sample bottle versus separate sample bottle sub-samples. Application of classical ANOVA showed that the relative combined standard uncertainty for each of the six sampling strategies ranged from 2.3–3.8%. This approach did not include an estimation of sampling bias. Application of robust ANOVA to the deep open ocean samples showed that contributions to the total variance were 0% from the different sample collection and filtration strategies, 42% from the sub-sample precision and 58% from between sub-sample measurements.